Molecular Basis of Multiple Sclerosis The Immune System - Martin, Roland; Lutterotti, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Despite major efforts by the scientific community over the years, our understanding of the pathogenesis or the mechanisms of injury of multiple sclerosis is still limited. Consequently, the current strategies for treatment and management of patients are limited in their efficacy. The mechanisms of tissue protection and repair are probably even less understood. One reason for these limitations is the enormous complexity of the disease and every facet of its pathogenesis, the mechanisms of tissue injury, the diagnostic procedures and finally the efficacy of treatments and their side effects. The aim of this book is to review the most recent advances made in this highly complex field.
The Genetics of Multiple Sclerosis -- Potential Triggers of MS -- Immunological Basis for the Development of Tissue Inflammation and Organ-Specific Autoimmunity in Animal Models of Multiple Sclerosis -- T-Cells in Multiple Sclerosis -- B Cells and Antibodies in MS -- Cooperation of B Cells and T Cells in the Pathogenesis of Multiple Sclerosis -- Role of NK Cells and Invariant NKT Cells in Multiple Sclerosis -- Antigen Processing and Presentation in Multiple Sclerosis -- Immune-Mediated CNS Damage -- Neuro-Immune Crosstalk in CNS Diseases -- Prospects for Antigen-Specific Tolerance Based Therapies for the Treatment of Multiple Sclerosis -- Immuno-Therapeutic Potential of Haematopoietic and Mesenchymal Stem Cell Transplantation in MS -- Multiple Sclerosis Therapies: Molecular Mechanisms and Future -- Examination of the Role of MRI in Multiple Sclerosis: A Problem Orientated Approach.
Keywords: Medicine; Human genetics; Immunology; Cytology; Biomedicine; Human Genetics; Cell Biology; Molecular Medicine; Immunology